Fiscal adjustments and business cycle synchronization - Luca Agnello; Guglielmo Maria Caporale; Ricardo M. Sousa (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Using a panel of annual data for 20 countries we show that synchronized fiscal consolidation (stimulus) programmes in different countries make their business cycles more closely linked, especially in the case of fiscal adjustments lasting 2 or 3 years. We also find: (i) little evidence of decoupling when an inflation targeting regime is unilaterally adopted; (ii) an increase in business cycle synchronization when countries fix their exchange rates and become members of a monetary union; (iii) a positive effect of bilateral trade on the synchronization of business cycles.
Keywords: C41; E62; 330; fiscal consolidation; fiscal stimulus; business cycle synchronization